Decentralized Clinical Trials: Bridging Innovation and Regulation - Kalidindi, Venkateswara Raju; Balaji, Gutturu Dheeraj; Mahalakshmi, Uda; Dinesh Babu, Sirilla; Priyanka, Badugu; Naga Lakshmi, Tekumudi Vasantha; Nori, Lakshmi Prasanthi (International Journal of Pharmaceutical Investigation, 2025)
Decentralized Clinical Trials (DCT) utilize digital health technologies, remote monitoring, and telehealth, eliminating the need for traditional in-person visits to clinical sites. This model provides significant benefits for both academic researchers and business stakeholders. Probably, better retention of patients could be a result of the simple nature and the increased pool of recruitment of patients across boundaries; more data collection with these digital tools, which entail wearables and apps is another benefit. More technologies include real-time data capturing, less burden in on-site visit, and more efficient and accessible. DCT can be hybrid models combining on-site and remote participation or stand-alone models carried purely online. Such trials would include telemedicine and cloud-platform solutions in handling vast data pools recovered from disparate sources. However, there are several disadvantages with DCT, some may have issues with technology, processing health data remotely poses privacy and security concerns, and regulation is largely unestablished in some locales. New waves of augmentation for AI-driven analytics call for improved data interpretation and predictive modelling in the further development of DCT. Proper regulatory frameworks, conducive to a decentralized approach, need to be drafted. As DCT would be much more accessible, they would not only bring clinical research to a larger population but also demand greater inclusiveness in terms of different patient demographics, thus offering better and more cost-effective studies.
Keywords: Decentralized clinical trials; Remote data collection; Web based study; Telehealth; Patient care; Regulations